O projeto poético literário cuírlombista de Tatiana Nascimento: uma análise das obras “lundu” e “07 notas sobre o apocalipse, ou poemas para o fim do mundo" - Silva, Maria Carolina Rodrigues Bastos da (2023)
This research proposes an analysis of the poetic project of tatiana nascimento from the works "lundu" and "07 notes on the apocalypse, or poems for the end of the world". In a manifesto entitled "Cuírlombismo literario: poesia negra LGBTQI desorbitando o paradigma da dor", the author proposes the neologism "cuírlombismo" to settle her poetry between the quilombo and queer or quare dimensions. So we have as specific objectives: to analyze the erotic representation of the black female body in this books; and to investigate to what extent the categories queer, quilombo, and the erotic dimensions and full enjoyment appear in the works as a way of confronting racism and colonial representations. To define the concept of quilombo, we used the proposals of Abdias do Nascimento (1980) and Beatriz do Nascimento (2006). The theorists propose that the quilombo, besides being a territory of struggle in diaspora, is a social political and economically organized field that has existed since the pre-diasporic period and passes, especially, through the body. As a corporeal dimension, Oyèrónké Oyěwùmí (2021), a Nigerian theorist, inquires that the diasporic body should be interpreted through a cosmoperception, in which all senses are part, because the body is the first to feel the world. Linked to this idea of corporeality, eroticism becomes a powerful dimension to transgress, through the sacred, the stereotypical practices that the colonial civilization stipulated for the black female body. According to Georges Bataille (2021), eroticism is a purely human dimension, since only human subjects can eroticize sexual activity, due to the need for continuity. This continuity is linked to the annulment of the abyss between one being and another. Analogous to this conception, the North American feminist theorist Audre Lorde (2009) inquires that eroticism works as sharing, so it escapes from the individualistic logic of beings. For her, at the source of the erotic, we can live fully, since jouissance will be everywhere, not only in sexual activity. However, inserted in this research as problematic is the need to discuss where gender and sexuality meet in a diasporic context. Therefore, tatiana nascimento uses queer and quare analytics (MORAES, 2020) in her poetic project. Thinking about eroticism as a necessary energy for a full life, in Tatiana nascimento's poetry, it was concluded that it appears through the African cosmoperception, figured in the images of the Orixás Oxum, Iemanjá and Iansã, and appeared through Itãs, which are evidenced throughout this text.